METAFORA KONSEPTUAL DALAM DISKURSUS ALAM DAN LINGKUNGAN HIDUP DI INDONESIA - Nia Kariyani (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
Unlike traditional metaphors that function as figurative language, conceptual metaphor serves to illustrate how humans, both collectively and individually, think about their everyday experiences, including their relationship with nature. Descriptive qualitative approach with observation and note-taking techniques, as well as image schemas analysis (Croft & Cruse, 2004) was applied to examine metaphorical headlines and news content from mass media such as Tempo, Merdeka, Suara Indonesia, and Antara News in early 2025. The analysis of five key metaphorical phrases; menggantungkan periuknya (hanging one’s pot), Brantas sekarat (Brantas dying), bumi sakit (sick earth), roda ekonomi (wheel of economy), and gunungan plastik (mountain of plastic) reveals distinct image schemas. The data suggested that different image schemas appeared from each mass media is to represent human experiences in relation to nature while simultaneously conveying criticism of ongoing ecological conditions. In line with previous studies, metaphors function not only as poetic imagination or the rhetorical flourish but also as cognitive tools that shape public understanding of environmental issues, reinforce narrative impact, and deliver critical messages in an implicit manner.